2020
DOI: 10.33021/icfbe.v1i1.1628
|View full text |Cite
|
Sign up to set email alerts
|

Use Intention of Fintech Services for E-Wallet Users: An Examination With an Extended Technology Acceptance Model

Abstract: <p><em>Financial Technology (Fintech) has increased, follows by various innovations that lead to efficient, safe, fast, and convenience. One type of Fintech in Indonesia is a non-cash payment using an electronic wallet (e-wallet). People started to do the transaction through their mobile using electronic wallet  (e-wallet)  in daily life. However, people still prefer to use cash transaction caused by the security concern also e-wallet application often experiences an error during transaction. Thus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
5
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 16 publications
5
5
3
Order By: Relevance
“…Perceived trust is also important for the users to reduce their concern on the cyber risk. The finding is in line with the findings of (Satyagraha, 2021;Armanditya & Rahmiati, 2020;Ridaryanto et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Perceived trust is also important for the users to reduce their concern on the cyber risk. The finding is in line with the findings of (Satyagraha, 2021;Armanditya & Rahmiati, 2020;Ridaryanto et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…In some previous studies, trust had been proven as an important factor affecting the adoption of online payment technologies (Chatterjee & Bolar, 2018;Sharma et al, 2018). Trust has significant positive relationship towards the use of ewallet (Armanditya & Rahmiati, 2020;Ridaryanto et al, 2020). Sharma et al (2018) found low level of trust will obstruct the technology adoption among mobile banking while Kumar et al (2018) showed positive effect of trust on the e-wallet adoption in developing countries.…”
Section: Hypotheses Development Perceived Trustmentioning
confidence: 99%
“…If FinTech users perceive its usefulness, it will positively impact their attitudes. This concept is supported by the findings of Armanditya & Rahmiati (2020) and Alkhowaiter (2022). Similarly, if the use of FinTech is perceived as beneficial for system users, they will be inclined to use FinTech.…”
Section: Effects Of Perceivedmentioning
confidence: 60%
“…Moreover, studies have indicated that attitude is positively impacted by perceived ease of use (Armanditya & Rahmiati, 2020;Yuhelmi et al, 2019;Wallace & Sheetz, 2014;Bashir & Madhavaiah, 2015a). According to research findings by Hafifah et al (2022), Audina et al (2021), and Damayanti et al (2022), The perception of FinTech's ease of use affects behavioral intention.…”
Section: Effects Of Perceivedmentioning
confidence: 99%
See 1 more Smart Citation